Genomics insights of candidiasis: mechanisms of pathogenicity and drug resistance - Huang, Xin; Dong, Qin; Zhou, Qi; Fang, Shitao; Xu, Yiheng; Long, Hongjie; Chen, Jingyi; Li, Xiao; Qin, Huaguang; Mu, Dan; Cai, Xunchao (Frontiers in Microbiology, 2025)
Candidiasis, a prevalent class of human infections caused by fungi belonging to the Candida genus, is garnering increasing attention due to its pathogenicity and the emergence of drug resistance. The advancement of genomics technologies has offered powerful tools for investigating the pathogenic mechanisms and drug resistance characteristics of Candida. This comprehensive review provides an overview of the applications of genomics in candidiasis research, encompassing genome sequencing, comparative genomics, and functional genomics, along with the pathogenic features and core virulence factors of Candida. Moreover, this review highlights the role of genomic variations in the emergence of drug resistance, further elucidating the evolutionary and adaptive mechanisms of Candida. In conclusion, the review underscores the current state of research and prospective avenues for exploration of candidiasis, providing a theoretical basis for clinical treatments and public health strategies.